Effect of Boerhavia diffusa and Bryophyllum calycinum Extracts on Urine Profile in Male Wistar Rats having Adenineinduced Chronic Kidney Disease - Singh, Madhu; Raval, Sunant K.; Modi, Rakeshkumar J.; Sadhu, Dashrath; Dave, Keshank (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on 62 adult healthy male Wistar rats (12-15 weeks of age) to examine the effect of herbal extracts on urine profile following adenine-induced chronic kidney disease (CKD). The rats were randomly divided into eight groups. Group I (n=6) was given only distilled water and served as healthy control. The rats of groups II to VIII (n=8 each) were given adenine @ 200 mg/kg body weight daily by oral gavage needle for 28 days to induce CKD. After 28th day, group II served as CKD positive group, while groups III and IV were given aqueous and alcoholic extract of Boerhavia diffusa (BD), group-V and VI with aqueous and alcoholic extract of Bryophyllum calycinum (BC) @ 300 mg/kg body weight daily for 42 days. Group VII was given bihebral aqueous extract of BC plus BD (1:1.5), while group VIII received bihebral alcoholic extract of BC and BD (1:1.5) @ 300 mg/kg body weight daily for 42 days. Urine parameters were studied on day 0, 28 and 70 of experiment to confirm the presence of CKD. Significantly (p <0.05) increased levels of urine output, urine specific gravity, urine calcium, phosphorus, and total protein, with decreased levels of urine creatinine and urine pH were observed in all CKD groups as compared to normal control group by 28th day. These changes were significantly (p <0.05) reverted to normal or near normal levels within next 42 days of daily administration of either single aqueous/alcoholic extract or a combination as biherbal extract (1:1.5), without statistical differences among formulations regarding their therapeutic/nephroprotective effect against CKD in terms of reducing the altered urine values